2015
DOI: 10.1155/2015/958695
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast Expression in Skin Wounds Is Enhanced by Collagen III Suppression

Abstract: Generally speaking, the excessive expression of myofibroblasts is associated with excessive collagen production. One exception is seen in patients and animal models of Ehlers-Danlos syndrome type IV in which the COL3A1 gene mutation results in reduced collagen III but with concurrent increased myofibroblast expression. This paradox has not been examined with the use of external drugs/modalities to prevent hypertrophic scars. In this paper, we injected the rabbit ear wound model of hypertrophic scarring with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Col I and Col III are metabolites of MFB, and are also valid markers for MFB. 24,25 We found that treatment of Jag1 siRNA significantly enhanced the expression of a-SMA, Collagen I, and Collagen III compared with the control group (P < 0.05; Fig. 2B, C, and D).…”
Section: Jagged 1 Inhibited the Differentiation Of Escs To Mfb In Vitromentioning
confidence: 71%
“…Col I and Col III are metabolites of MFB, and are also valid markers for MFB. 24,25 We found that treatment of Jag1 siRNA significantly enhanced the expression of a-SMA, Collagen I, and Collagen III compared with the control group (P < 0.05; Fig. 2B, C, and D).…”
Section: Jagged 1 Inhibited the Differentiation Of Escs To Mfb In Vitromentioning
confidence: 71%
“…Col I and Col III are metabolites of MFB, and are also valid markers for MFB [35,36]. We found that the expression of α-SMA, Col I, and Col III was significantly lower after anti-miR-203 treatment compared with Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry control (P < 0.05; Fig.…”
Section: Mir-203 Promoted the Formation Of Mfb In Vitromentioning
confidence: 80%
“…Her symptoms included joint hypermobility affecting large and small joints, arthralgia, soft "velvety" skin as well as vasomotor instability exemplified by orthostatic hypotension. In Ehlers-Danlos vascular type, collagen III is decreased [9]. Al-Qattan et al proposed a paradoxical increase in myofibroblast expression when collagen III expression is decreased [9].…”
Section: Discussionmentioning
confidence: 99%
“…In Ehlers-Danlos vascular type, collagen III is decreased [9]. Al-Qattan et al proposed a paradoxical increase in myofibroblast expression when collagen III expression is decreased [9]. Compared to the other types of EDS, vascular type EDS is known to develop postoperative scar hypertrophy and spontaneous skin keloid-like lesions [10,11].…”
Section: Discussionmentioning
confidence: 99%